Antioxidant Activity With Total Phenolic Constituents From Aerva Tomentosa Forsk. - ASHISH SETHI; R. A. SHARMA (International Journal of Pharma and Bio Sciences, 2011)
In the present study, antioxidant potential of the different extract of the whole plant of Aerva tomentosa Forsk. was evaluated by using 2, 2-diphenyl-1-picrylhydrazyl (DPPH) scavenging assay and total phenolic contents was analyzed using the Folin-Ciocalteu reagent method. The methanol extract showed significant activity in antioxidant assay compared to other successive extracts such as petether, dichloromethane, ethylacetate and aqueous. In DPPH scavenging assay the RC50 value of the methanol extract was found to be 6.0 µg/ml. The highest amount of total phenolic contents was found in methanol soluble fraction (34.5 ± 0.726 mg gallic acid equivalent/g extract). These results suggest that there was a direct correlation between total phenolics and antioxidant activities which could introduce phenols as the main antioxidant of Aerva tomentosa extracts and offering effective protection from free radicals.